Baseline Dual Energy Computed Tomography Urate Volume Predicts Fulfillment of Gout Remission After Two Years of Urate-Lowering Therapy - Tabi-Amponsah, Adwoa Dansoa; Stewart, Sarah; Gamble, Greg; Doyle, Anthony J; Billington, Karen; Son, Chang-Nam; Latto, Kieran; Stamp, Lisa K; Taylor, William J; Horne, Anne; Dalbeth, Nicola (Wiley, 2024)
OBJECTIVE: This study aimed to identify variables that predict gout remission in people with erosive gout receiving urate-lowering therapy. METHODS: We analysed data from a 2-year, double-blind randomized-controlled trial of people with erosive gout, randomized to a serum urate target of <0.20mmol/l or <0.30mmol/l using oral urate-lowering therapies. All participants had dual energy CT (DECT) scans of the feet and ankles at baseline. The proportion of participants achieving gout remission according to the 2016 preliminary gout remission criteria and simplified gout remission criteria (without the patient reported outcomes) was analyzed. Logistic regression models were used to evaluate predictors of gout remission in Year 2. RESULTS: The preliminary gout remission criteria were fulfilled in 11/97 (11%) participants at Year 1 and 21/92 (23%) participants at Year 2. The simplified criteria were fulfilled in 26/97 (27%) participants in Year 1 and 40/92 (44%) participants in Year 2. In multivariable regression models, baseline DECT monosodium urate crystal volume was the only significant independent predictor of gout remission at Year 2, using either criteria. Each one cm3 increase in the baseline DECT monosodium urate crystal volume decreased the odds of fulfilling the 2016 preliminary gout remission criteria (0.65 [95% CI 0.46-0.93], p=0.02), and the simplified gout remission criteria (0.57 [95% CI 0.41-0.78], p<0.001). CONCLUSIONS: In people with erosive gout on urate-lowering therapy, higher baseline DECT monosodium urate crystal volume is associated with lower odds of gout remission after two years of treatment, defined by either the preliminary gout remission criteria or simplified gout remission criteria.
Keywords: 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; Clinical Research; Clinical Trials and Supportive Activities; 6.1 Pharmaceuticals; Inflammatory and immune system; 1103 Clinical Sciences; 1117 Public Health and Health Services; 1701 Psychology; 3202 Clinical sciences; 4201 Allied health and rehabilitation science; Humans; Gout; Male; Female; Uric Acid; Gout Suppressants; Middle Aged; Remission Induction; Tomography, X-Ray Computed; Aged; Double-Blind Method; Treatment Outcome; Predictive Value of Tests; Time Factors; Adult